2005
DOI: 10.2131/jts.30.265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanol Extracts of Caesalpinia Bonducella and Bauhinia Racemosa on Hematology and Hepatorenal Function in Mice

Abstract: The aim of the present investigation deals with the hematology and hepatorenal function of Caesalpinia bonducella Flem. and Bauhinia racemosa Lam. belonging to the Family: Caesalpiniaceae, and used in the traditional system of medicine. The tribal people of Kolli Hills, Tamil Nadu, India, use the leaves of Caesalpinia bonducella and the stem bark of Bauhinia racemosa in combination with some other herbs for the treatment of various tumors, liver disorders, inflammation and some other diseases. In ancient Ayurv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
5
17
0
1
Order By: Relevance
“…This is in agreement with other published works (Kumar et al, 2005;Sagar and Vidyasagar, 2010). However, higher extract treatment doses of 400 to 1600 mg/kg bwt were toxic to the experimental animals as there were significant increases in relative organ weights (Table VI) as well as in the activities of alanine and aspartate aminotransferases (Table VII), and in the concentrations of plasma total bilirubin, plasma indirect bilirubin, plasma uric acid, plasma urea, plasma triglyceride and plasma cholesterol (Tables VII, VIII Feron et al (1973) reported that in sub-acute toxicity experiments, the relative organ weight is a useful index of toxicity.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with other published works (Kumar et al, 2005;Sagar and Vidyasagar, 2010). However, higher extract treatment doses of 400 to 1600 mg/kg bwt were toxic to the experimental animals as there were significant increases in relative organ weights (Table VI) as well as in the activities of alanine and aspartate aminotransferases (Table VII), and in the concentrations of plasma total bilirubin, plasma indirect bilirubin, plasma uric acid, plasma urea, plasma triglyceride and plasma cholesterol (Tables VII, VIII Feron et al (1973) reported that in sub-acute toxicity experiments, the relative organ weight is a useful index of toxicity.…”
Section: Discussionsupporting
confidence: 94%
“…The liver, being the detoxification organ of mammals, and the kidney, being the most important excretory organ in the body, might be susceptible to the toxic effects of extracts of C. bonduc at higher doses. This is supported by the report of Kumar et al (2005), who reported the associated toxicity of anticancer agents and plants rich in flavonoids on the liver and kidney.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In turn, this may lead to low growth, notably reduced mean body weight. Kumar 28 also reported that weight of mice treated with methanol leaf extract of Caesalpinia bonducella and Bauhinia racemosa decreased significantly as a reflection of low growth.…”
mentioning
confidence: 98%